1998
DOI: 10.1046/j.1365-2710.1998.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring of tobramycin: once‐daily versus twice‐daily dosage schedules

Abstract: This small study suggests that a once-daily dosing regimen of tobramycin is at least as effective as and is no more and possibly less toxic than the twice-daily regimen. Using a single-dose therapy, peak concentration determination is not necessary, only trough samples should be monitored to ensure levels below 2 microg/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Population PK analyses were performed using WinNonMix (version 2.0.1, Pharsight (Mountain View, CA, USA, 2000), which uses non‐linear mixed effect modelling to derive parameter estimates based upon sparse data. Previous work demonstrated that tobramycin pharmacokinetics can be modelled as a one‐compartment model 26–28 . During model development, both one‐ and two‐compartment models were tested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population PK analyses were performed using WinNonMix (version 2.0.1, Pharsight (Mountain View, CA, USA, 2000), which uses non‐linear mixed effect modelling to derive parameter estimates based upon sparse data. Previous work demonstrated that tobramycin pharmacokinetics can be modelled as a one‐compartment model 26–28 . During model development, both one‐ and two‐compartment models were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work demonstrated that tobramycin pharmacokinetics can be modelled as a one-compartment model. [26][27][28] During model development, both one-and two-compartment models were tested. The one-compartment model was chosen as the two-compartment model did not demonstrate any improvement in the fit of these data.…”
Section: Population Pharmacokinetics Analysismentioning
confidence: 99%
“…23,24 Much of the literature emphasizes the importance of high peak serum drug concentrations, with the most important aspect of clinical success being related to the peak:MIC ratio. 3,14,15 Bailey et al 23 compared outcomes with once-daily and multiple-daily aminoglycoside dosing in a metaanalysis of 22 randomized controlled trials. The outcomes assessed were clinical effectiveness, bacteriologic efficacy, nephrotoxicity, and ototoxicity.…”
Section: Clinical Efficacy Of Once-daily Dosingmentioning
confidence: 99%
“…The use of once-daily dosing of gentamicin has been shown to be less nephrotoxic and cost effective. [34][35][36] Patients who had exposure to AG previously can be predisposed to nephrotoxicity during subsequent regimens. 37 Finally, Bertino et al confirmed several significant risk factors in 1489 patients and are listed in Table 1.…”
Section: Gram-negative Infectionsmentioning
confidence: 99%